Assessing the associations of inflammatory bowel disease and hepatitis B virus infections with two-sample bidirectional mendelian randomization - Ping Han; Chaohui Wang; Yan Qiu (Taylor & Francis Group, 2024)
Previous observational studies have suggested an association between inflammatory bowel disease (IBD) and chronic hepatitis B virus infection (CHB). This study aimed to determine whether there is a causal association between IBD and CHB using a bidirectional two-sample Mendelian randomization (MR) design. Independent genetic variants were extracted from public genome-wide association studies (GWAS) for CHB (145 cases 351,740 controls) to estimate the causal effects on inflammatory bowel disease (12882 cases 21,770 controls) and its two subtypes: ulcerative colitis (69968 cases 20,464 controls) and Crohn's disease (5956 cases 14,927 controls). The instrumental variables (IVs) were selected with p < 5.0 × 10−8, linkage disequilibrium LD, and F-statistic >10. Before MR analysis, sensitivity analysis was conducted to verify the robustness, including Cochran's Q test, MR-Egger intercept test, MR-PRESSO, leave-one-out analysis, and MR-Steiger test of directionality. Odds ratio (OR) with 95% confidence intervals (CI) was used to express MR results. No associations were detected for the causal effect of genetically predicted IBD and Crohn disease (CD) on CHB (p value for IVW: 0.87 and 0.48, respectively). Ulcerative colitis (UC) reduced the risk of CHB (0.91[0.85 0.98], p < 0.001). No causal relationship was found between hepatitis B virus infections and IBD and its subtypes (UC and CD) (p values for IVW: 0.189, 0.328, and 0.065, respectively). Despite some observational associations, our study did not support a causal association between IBD and an elevated risk of CHB. UC appeared to reduce the risk of CHB infection.